2002
DOI: 10.1152/ajprenal.00347.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostanoids in regulation of the renin-angiotensin-aldosterone system by salt intake

Abstract: Kurtz. Role of prostanoids in regulation of the renin-angiotensin-aldosterone system by salt intake. Am J Physiol Renal Physiol 283: F294-F301, 2002. First published February 26, 2002 10.1152/ajprenal.00347.2001.-We investigated the effect of cyclooxygenase (COX) activity on the regulation of the renin-angiotensin-aldosterone system by salt intake. Therefore, Sprague-Dawley rats were subjected to different salt diets [0.02, 0.6, and 8% NaCl (wt/wt)] and treated with the selective COX-2 inhibitor rofecoxib (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
29
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
10
29
1
Order By: Relevance
“…On the other hand, an up to 3-wk treatment with the COX-2 inhibitor rofecoxib did not alter renin mRNA or plasma renin activity in rats (14,15). A striking difference between these and the present studies is the marked upregulation of COX-2 expression in the rofecoxib-treated rats (14). It is possible that the pharmacological approach may not abolish local PG production, either because of accessibility problems or because the upregulated COX-2 expression enhances enzyme capacity that, in part, compensates for reduced enzyme activity.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, an up to 3-wk treatment with the COX-2 inhibitor rofecoxib did not alter renin mRNA or plasma renin activity in rats (14,15). A striking difference between these and the present studies is the marked upregulation of COX-2 expression in the rofecoxib-treated rats (14). It is possible that the pharmacological approach may not abolish local PG production, either because of accessibility problems or because the upregulated COX-2 expression enhances enzyme capacity that, in part, compensates for reduced enzyme activity.…”
Section: Discussionmentioning
confidence: 76%
“…The COX-2 inhibitor SC-58125 has been found to reduce plasma renin activity and renal renin mRNA levels in low salt-fed and renal hypertensive mice (9). On the other hand, an up to 3-wk treatment with the COX-2 inhibitor rofecoxib did not alter renin mRNA or plasma renin activity in rats (14,15). A striking difference between these and the present studies is the marked upregulation of COX-2 expression in the rofecoxib-treated rats (14).…”
Section: Discussionmentioning
confidence: 98%
“…celecoxib, or nimesulide, attenuate an increase in renin secretion and renin expression in response to renovascular hypertension (8,14,25,28,37), low salt intake (8,16,18,29,38), and angiotensin II inhibition (5, 6, 19). It has been suggested that this striking difference between the various COX-2 inhibitors may be due to a lower accessibility of rofecoxib or celecoxib at the level of macula densa cells and/or the juxtaglomerular apparatus, which may lead to insufficiently high enough drug levels for a complete inhibition of local prostaglandin production (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies with COX-2-deficient mice and with selective COX-2 inhibitors produced conflicting findings. It has been found that pharmacological inhibition of COX-2 with SC-58236 and SC-58125 as well as COX-2 deficiency attenuate the increase in renin release and renin expression due to renovascular hypertension, low salt intake, and angiotensin II inhibition (5,6,8,37,38), whereas commercially available COX-2 inhibitors, like rofecoxib and celecoxib, did not affect the stimulation of the renin system in response to these stimuli (14,18,19,25,28,29). Recently, it has been reported that COX-2 deficiency reduces basal renin expression and renin release but does not attenuate the secretion of renin in response to acute stimuli (23).…”
mentioning
confidence: 99%
“…Evidence from studies with spontaneously hypertensive rats using indomethacin and PGH 2 /TXA 2 receptor blockers (e.g., SQ 29,548) indicate that endothelium-derived PGH 2 and TXA 2 are contractile factors in intrarenal arteries that may underlie impaired relaxation to ACh (Dai et al, 1992;FuXiang et al, 1992). Numerous studies have addressed the role of prostaglandins during changes in dietary sodium (Hocherl et al, 2002), but the impact on small vessels is less well known. In the present study, indomethacin also partially restored ACh induced relaxation of renal arteries of lisinopril treated rats during low sodium.…”
Section: Discussionmentioning
confidence: 99%